Advanced Copper Oxide Chemical and Green Synthesis: Characterization and Antibacterial Evaluation - Ecaterina Magdalena Modan; Adriana-Gabriela Schiopu; Sorin Georgian Moga; Denis Aurelian Negrea; Daniela Istrate; Ion Ciuca; Mihai Oproescu (Crystals)
Recent advancements in nanotechnology have improved the application of copper oxide (CuO) nanostructures, known for their diverse antibacterial, electrical, catalytic, optical, and pharmacological properties, which depend on nanoparticle morphology. This study investigated two synthesis methods for structured CuO: microwave-assisted hydrolysis and ultrasound using copper acetate and KOH, and an eco-friendly method involving cholesterol-free egg white albumin and Solanum lycopersicum extract. Characterization techniques, including XRD, FTIR, and SEM-EDS, were utilized to analyze the produced CuO. XRD confirmed high-purity monoclinic CuO structures in the sample obtained via the chemical method, while characteristic peaks of tenorite and dolerophanite were observed in the albumin-synthesized sample. ATR-FTIR analysis revealed O-H stretching bands around 3400 cm−1, indicating adsorbed H-OH or -OH and strong Cu-O bond peaks at 434 cm−1. The CuO synthesized via microwave and ultrasound methods displayed superior crystallinity compared to commercial CuO. SEM illustrated various morphologies, such as flakes, microspheres, and irregular polyhedra, influenced by the presence of proteins and organic acids. Antibacterial tests demonstrated the effective inhibition of Escherichia coli and Enterococcus faecalis, confirming the potential of CuO as a promising antibacterial agent. Overall, the findings highlight the effectiveness of green chemistry in developing crystalline CuO for various applications.